Research on Work-Related Injury Insurance Issues for Online Car-Hailing Drivers Based on Occupational Risk Theory - Su, Xueping (Journal of Social Science and Humanities, 2025)
With the development of the Internet era with sharing characteristics and the increasing demand for convenient travel, the online car-hailing industry, which relies on the Internet platform as an operating base, has developed rapidly in China. As of June 2022, there are 300 online car-hailing platforms in China, the scale of online car-hailing users has reached 405 million, and the number of online car-hailing orders has reached 6.96 billion. More and more workers are beginning to join the group of online car-hailing drivers to cope with the difficulties of finding a job. However, unlike ordinary employment methods, employment on online car-hailing platforms involves multiple parties such as operators, laborers, and labor users. The relationship is complicated, and there are characteristics such as flexibility in employment methods, diversity in service practices, and ambiguity in the subject of employment. Under the premise that the labor relationship between online car-hailing drivers and online car-hailing platforms has not yet been clarified, there is a problem of lack of work-related injury insurance for online car-hailing drivers, which makes them unable to be protected when facing labor disputes, which is not conducive to the continuous, benign and healthy development of the online car-hailing market. As the number of platform employees represented by online ride-hailing platform drivers continues to increase, whether the work-related injury rights and interests of these practitioners can be effectively protected is directly related to the stability of the development of China’s platform employment model. Based on this, this paper starts with the theory of occupational risk and studies the work-related injury insurance issues of online ride-hailing drivers.